Current Approaches to Treatment and Protein Intake Management in Pre-Dialysis Chronic Kidney Disease: Impact on Physical Exercise - Olga Beata Wieczorek; Daria Aleksandrowicz; Marta Głąbień; Zofia Jakubczak; Paweł Miłkowski; Maria Weronika Zimniak; Aneta Kondratowicz; Patryk Śliwiak; Karolina Kusiak; Anna Kuśnierz (Quality in Sport, 2024)
Chronic kidney disease (CKD) is the 8th most common condition in the modern world. Unfortunately, it becomes more and more frequent and constitutes a significant global health problem, affecting millions of people worldwide. Therefore, its treatment is an important topic among researchers all over the world. It has been the subject of many trials, so it will eventually be as effective, secure, and comfortable for patients as it possibly can be. That is why updating and assembling current knowledge is the key to organizing information. This paper focuses on pharmacological treatment and nutritional guidelines for CKD pre-dialysis patients, as well as physical activity outcomes. It aims to summarize this knowledge, educate, and help doctors in their daily clinical work.